2012
DOI: 10.1089/biores.2012.0209
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Neural Progenitor Cells in Functionalized Hydrogel Matrices

Abstract: Hydrogel-based three-dimensional (3D) scaffolds are widely used in the field of regenerative medicine, translational medicine, and tissue engineering. Recently, we reported the effect of scaffold formation on the differentiation and survival of human neural progenitor cells (hNPCs) using PuraMatrix™ (RADA-16) scaffolds. Here, we were interested in the impact of PuraMatrix modified by the addition of short peptide sequences, based on a bone marrow homing factor and laminin. The culture and differentiation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Anti-apoptotic BCL-2 increases and predominantly co-localizes with mitochondria during the differentiation of neural ReNcell VM progenitor cells, which is in agreement with published literature (Merry et al, 1994;Liedmann et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Anti-apoptotic BCL-2 increases and predominantly co-localizes with mitochondria during the differentiation of neural ReNcell VM progenitor cells, which is in agreement with published literature (Merry et al, 1994;Liedmann et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…We have demonstrated that a powerful advantage of 3D culture for modeling AD is that it provides a local environment that promotes aggregation of β‐amyloid, which can trigger pathogenic cascades, including NFT . In addition, other studies have shown that 3D conditions more closely mimic in vivo environments and can accelerate neuronal differentiation and neural network formation . Neurons grown in a 2D environment are able to spread freely across the surface of the glass or plastic surface, but they have no support for vertical growth, which can lead to unintended apical‐basal polarity rather than the more accurate neuronal stellar morphology .…”
Section: Why Is 3d Better Than 2d For Modeling Ad?mentioning
confidence: 99%
“…The various advantages offered by 3D over 2D cellular cultures have been well acknowledged in recent literature (Pampaloni, Reynaud, & Stelzer, ; Ravi, Paramesh, Kaviya, Anuradha, & Solomon, ), especially in the provision of cues influencing cell structure, adhesion, proliferation, signalling, and mechanotransduction (Baker & Chen, ). This is also relevant in neuronal cultures, where a 3D substrate helps improve both cell yield (Liedmann, Frech, Morgan, Rolfs, & Frech, ) and cell differentiation (Zhang et al, ) in comparison with traditional 2D dishes. Figure highlights the key approaches utilized by researchers in realizing a 3D environment for in vitro cell culture, which is relevant in the context of neurodegenerative disease modelling and neurotherapeutics testing (Edelman & Keefer, ; Hopkins et al, ; Ko & Frampton, ).…”
Section: In Vitro Models Of Admentioning
confidence: 99%